Cysteine proteases in protozoan parasites - Siqueira-Neto, Jair L.; Debnath, Anjan; McCall, Laura-Isobel; Bernatchez, Jean A.; Ndao, Momar; Reed, Sharon L.; Rosenthal, Philip J. (PLoS neglected tropical diseases, 2018)
Cysteine proteases (CPs) play key roles in the pathogenesis of protozoan parasites, including cell/tissue penetration, hydrolysis of host or parasite proteins, autophagy, and evasion or modulation of the host immune response, making them attractive chemotherapeutic and vaccine targets. This review highlights current knowledge on clan CA cysteine proteases, the best-characterized group of cysteine proteases, from 7 protozoan organisms causing human diseases with significant impact: Entamoeba histolytica, Leishmania species (sp.), Trypanosoma brucei, T. cruzi, Cryptosporidium sp., Plasmodium sp., and Toxoplasma gondii. Clan CA proteases from three organisms (T. brucei, T. cruzi, and Plasmodium sp.) are well characterized as druggable targets based on in vitro and in vivo models. A number of candidate inhibitors are under development. CPs from these organisms and from other protozoan parasites should be further characterized to improve our understanding of their biological functions and identify novel targets for chemotherapy.